Effect of Teucrium polium aqueous extract on mice sperm (Journal of the College of Basic Education, 2022)
There are several reports about using Teucrium polium (TP) in traditionalmedicine mainly for its antipyretic, antibacterial, antiinflammatory,antioxidant, antialcerogenic, antispasmodic, anti diabetic, hepatotoxicityand for fertility. Male mice was orally administrated by two concentration(50 mg/kg, 100 mg/kg) of TP aqueous extract to study the effect of thisaqueous extract for period of time on fertility (live sperm, motility andabnormality). The result showed that there is significant difference(P<0.05) (in live sperm and motile sperm) between group treated with100 mg/kg with control, while there was a significant difference inabnormality between the treated groups with the control. The increase intestes weight also indicate the positive effect referring to some TPconstituents in the treated groups. The investigation has shown that theextract possesses promising fertility property which can be exploited infertility therapy.